Tuberculosis contact investigation with a new, specific blood test in a low-incidence population containing a high proportion of BCG-vaccinated persons - Meywald-Walter K; Lange C; Nienhaus A; Diel R; Forßbohm M; Schaberg T (Respiratory Research, 2006)
Abstract Background BCG-vaccination can confound tuberculin skin test (TST) reactions in the diagnosis of latent tuberculosis infection. Methods We compared the TST with a Mycobacterium tuberculosis specific whole blood interferon-gamma assay (QuantiFERON®-TB-Gold In Tube; QFT-G) during ongoing investigations among close contacts of sputum smear positive source cases in Hamburg, Germany. Results During a 6-month period, 309 contacts (mean age 28.5 ± 10.5 years) from a total of 15 source cases underwent both TST and QFT-G testing. Of those, 157 (50.8%) had received BCG vaccination and 84 (27.2%) had migrated to Germany from a total of 25 different high prevalence countries (i.e. >20 cases/100,000). For the TST, the positive response rate was 44.3% (137/309), whilst only 31 (10%) showed a positive QFT-G result. The overall agreement between the TST and the QFT-G was low (κ = 0.2, with 95% CI 0.14.-0.23), and positive TST reactions were closely associated with prior BCG vaccination (OR 24.7; 95% CI 11.7–52.5). In contrast, there was good agreement between TST and QFT-G in non-vaccinated persons (κ = 0.58, with 95% CI 0.4–0.68), increasing to 0.68 (95% CI 0.46–0.81), if a 10-mm cut off for the TST was used instead of the standard 5 mm recommended in Germany. Conclusion The QFT-G assay was unaffected by BCG vaccination status, unlike the TST. In close contacts who were BCG-vaccinated, the QFT-G assay appeared to be a more specific indicator of latent tuberculosis infection than the TST, and similarly sensitive in unvaccinated contacts. In BCG-vaccinated close contacts, measurement of IFN-gamma responses of lymphocytes stimulated with M. tuberculosis-specific antigen should be recommended as a basis for the decision on whether to perform subsequent chest X-ray examinations or to start treatment for latent tuberculosis infection.